-19=5(1+3x)-4(6-5x)

Simple and best practice solution for -19=5(1+3x)-4(6-5x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -19=5(1+3x)-4(6-5x) equation:


Simplifying
-19 = 5(1 + 3x) + -4(6 + -5x)
-19 = (1 * 5 + 3x * 5) + -4(6 + -5x)
-19 = (5 + 15x) + -4(6 + -5x)
-19 = 5 + 15x + (6 * -4 + -5x * -4)
-19 = 5 + 15x + (-24 + 20x)

Reorder the terms:
-19 = 5 + -24 + 15x + 20x

Combine like terms: 5 + -24 = -19
-19 = -19 + 15x + 20x

Combine like terms: 15x + 20x = 35x
-19 = -19 + 35x

Add '19' to each side of the equation.
-19 + 19 = -19 + 19 + 35x

Combine like terms: -19 + 19 = 0
0 = -19 + 19 + 35x

Combine like terms: -19 + 19 = 0
0 = 0 + 35x
0 = 35x

Solving
0 = 35x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-35x' to each side of the equation.
0 + -35x = 35x + -35x
Remove the zero:
-35x = 35x + -35x

Combine like terms: 35x + -35x = 0
-35x = 0

Divide each side by '-35'.
x = 0

Simplifying
x = 0

See similar equations:

| -2(6-2n)=5(n-1) | | 4(W+1)-7=3(7-1)+W | | 5x+8x-40=80-7x | | 4(6+7)=4*6+x*7 | | s=-16t^2+128t+144 | | 18xy-3x-19xy= | | 24x^2+91x+72=0 | | 5G/7=18 | | -14.1+18.3= | | 4x+9=12+3x | | -7/2-2x=-1/2 | | ((4x^2)-2x+6)/(2x-3) | | 65-7x=2x+23 | | -5(k+3)+4k=3(k-5) | | 80=5*2b | | -2-(6)= | | 25x+30y=120 | | .1(.1x+.9)= | | 3y=3y+18 | | -6(x-2)=12-3x | | 15+6x=25+5x | | 5x-2(-x-6)=-37 | | x^2=4x-6 | | 3+8q=5+7q | | 3x^2+4-10=0 | | x-174=-4x+1 | | 2m+10=16 | | Ei=5r+18 | | -16.04-(-9.57)= | | log(4x+1)+log(x+2)=1 | | 3m+(-10)=8m+(-10) | | -32.7+(-0.2)= |

Equations solver categories